Tracking global research on knowledge, attitudes, skills and community participation in ecotourism and conservation: A systematic literature review base on Scopus database - Wahyu Prihanta; Yus Mochamad Cholily; Abdulkadir Rahardjanto (University of Muhammadiyah Malang, 2025)
This study presents a systematic literature review (SLR) of global research trends on knowledge, attitudes, skills, and community participation in ecotourism and conservation, using data from the Scopus database. The review spans publications from 1994 to 2024 and is guided by six research questions focusing on publication trends, subject areas, thematic patterns, keyword relevance, conceptual structure, and emerging research directions. The methodology involved a structured search using specific inclusion criteria via Scopus and Scopus AI, resulting in 50 final articles. Data were analyzed using the “Analyze Search Results” feature in Scopus and visualized using VOS viewer to map co-occurrence patterns and concept networks. The findings highlight a significant growth in research since 2015, with dominant themes such as stakeholder engagement, sustainable ecotourism management, and community-based development. Emerging themes include mangrove ecotourism, natural resource integration, and post-COVID-19 tourism dynamics. The study identifies that environmental knowledge and positive attitudes significantly enhance community participation and conservation outcomes. This review contributes a comprehensive framework for understanding the interplay between ecotourism and community empowerment. It offers practical insights for policymakers and practitioners and outlines future research directions, including participatory governance, local capacity building, and the integration of indigenous knowledge in sustainable tourism strategies.